Effects of fungicide on meiosis of tomato (Lycopersicon esculentum Mill.) (Bangladesh Journal of Botany, 2008)
The effects of Equation Pro (22.5 % Famoxadone + 30% Cymoxanil) fungicide applied to tomato grown in greenhouse at recommended dosage (40 g/100 l tap water) by manufacturing company and double the recommended dosage (80 g/100 l tap water) were investigated on pollen meiosis. It was observed that the fungicide used in trial applications caused anomalies in pollen meiosis in parallel with the increase in dosage. It is obvious that this condition will have a negative effect on pollen fertility.